2007
DOI: 10.1007/s10546-007-9173-x
|View full text |Cite
|
Sign up to set email alerts
|

Large-eddy simulation of plant canopy flows using plant-scale representation

Abstract: Turbulent flow in a corn canopy is simulated using large-eddy simulation (LES) with a Lagrangian dynamic Smagorinsky model. A new numerical representation of plant canopies is presented that resolves approximately the local structure of plants and takes into account their spatial arrangement. As a validation, computational results are compared with experimental data from recent field particle image velocimetry (PIV) measurements and two previous experimental campaigns. Numerical simulation using the traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 43 publications
1
52
0
Order By: Relevance
“…Three specific functional forms are postulated. First, C d is a constant, an assumption used in many LES studies (e.g., Shaw and Schumann 1992;Su et al 1998;Patton et al 2003;Yue et al 2007b;Dupont and Brunet 2008;Gavrilov et al 2013). DNS results suggest that a constant instantaneous drag coefficient is a good model for rigid canopies (Santiago et al 2008).…”
Section: Approaches To Estimate the Instantaneous Drag-wind Relationshipmentioning
confidence: 99%
See 2 more Smart Citations
“…Three specific functional forms are postulated. First, C d is a constant, an assumption used in many LES studies (e.g., Shaw and Schumann 1992;Su et al 1998;Patton et al 2003;Yue et al 2007b;Dupont and Brunet 2008;Gavrilov et al 2013). DNS results suggest that a constant instantaneous drag coefficient is a good model for rigid canopies (Santiago et al 2008).…”
Section: Approaches To Estimate the Instantaneous Drag-wind Relationshipmentioning
confidence: 99%
“…The distributed drag force depends on the leaf area density, the velocity, and the local drag coefficient. This framework has been used in a range of modelling approaches including one-dimensional first-and second-order closure (Wilson and Shaw 1977;Katul 1998;Pinard and Wilson 2001;Poggi et al 2004a;Katul et al 2011), Reynolds-averaged Navier-Stokes (RANS; Dupont et al 2006) and large-eddy simulation (LES; Shaw and Schumann 1992;Su et al 1998;Patton et al 2003;Shaw and Patton 2003;Yue et al 2007b;Dupont and Brunet 2008;Gavrilov et al 2013;Pan et al 2014a). Turbulence statistics predicted by these models are highly sensitive to the parametrization schemes employed for the local mean and instantaneous drag coefficients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LES was first applied to the canopy turbulence by Shaw and Schumann (1992) and Kanda and Hino (1994) and then by many authors (Dwyer et al 1997;Shen and Leclerc 1997;Su et al 1998Su et al , 2000Patton et al 1998;Fitzmaurice et al 2004;Watanabe 2004;Yue et al 2007). All these studies showed the LES technique is an e¤ective tool for investigating the statistics, energetics and threedimensional structures of canopy turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…6. CI-This model was inspired by the work of (Yue et al, 2007) who advocated the use of a plant scale approach when considering canopy flows. Each tree was modelled as an individual cylinder of height and diameter equal to the height and maximum diameter of the actual tree represented, as shown in Fig.…”
Section: Representation Of the Canopy In The Cfd Modelmentioning
confidence: 99%